História natural de Sporophila hypoxantha cabanis, 1851 (aves: emberizidae) em campos de altitude no sul do brasil - Franz, Ismael (2012)
We studied the natural history of the Tawny-bellied Seedeater (Sporophila hypoxantha), an important and poorly known species from South American grasslands, regarding its biology and ecology. Data were collected during three breeding seasons (from November to March in 2007/2008, 2008/2009 and 2009/2010) on steep dry fields along the Lava-Tudo River at Coxilha Rica (Lages) and Estância do Meio (São Joaquim) in southeastern Santa Catarina State, Brazil (28° 18 S, 50º 17 W; 800-1000 m a.s.l.). We monitored 69 nests, every 2-6 days, to evaluate aspects of the chronology; territoriality; nesting; habitat selection; features of the nest, eggs and nestlings; parental care; nest fate (reproductive success or failure) and daily nest survival. Males arrive in the first week of November and then initiate the establishment and defense of their territories. With the arrival of females some days later, the selection of mates and nesting sites begins. The number of active nests peaked in the second half of November. Females construct the nest by themselves, with the males watching close by, over a period of 3-6 days. Selected sites are located on flat terrain and are characterized by the presence of a rich middle vegetation stratum such as shrubs of Vernonia chamaedrys, Eupatorium polystachyum, and Baccharis caprariifolia and clumps of Andropogon lateralis. Habitats with a dense high stratum, steep slope and small trees such as Escallonia megapotamica were avoided. The preferred habitats occur in areas of moderate intensity of grazing and little burning. The small nests are in the shape of an open cup, made with thin stems of grasses such as Eragrostis polytricha, on bushes (mainly V. chamaedrys and E. polystachyum, 66%), at a mean height of 41.9 ± 0.8 cm from the ground. Clutch size is two (91%) to three eggs. Incubation, performed by the female, lasts for 12 days. During this period, the female incubates for 60% of the time, and each visit takes between 20 and 31 min. Nestlings are fed by the female during the first days of life, and from the fifth day, the male begins to assist with feeding. A mean of 4.6 ± 0.7 and 8.95 ± 1.8 visits were performed to feed nestlings 1-4 and 6-9 days old, respectively. Juveniles become independent after 30 days. The basic parameters of reproductive biology resemble those described for the resident population of the province of Formosa, Argentina, except for having a shorter season, building nests more rapidly, and shorter mean durations of visits and parental care. Forty percent of 55 nests were successful. Mayfield success was 25%. Predation was the main cause of nest failure (55%), followed by abandonment, subcutaneous infestation by larvae of Philornis seguyi, cattle trampling, and grass burning. The daily survival rate (DSR) was higher in the incubation period (0.945) than in the nestling period (0.927). This pattern was corroborated by analysis using the MARK program, which found a sharp decrease in DRS during the 21 days of nesting (12 incubation days plus 9 nestling days). This may be related to the nesting activity (increased during the final stages of the cycle) as predicted by the hypothesis of the Alexander Skutch. There was a gradual decline in DSR during the breeding season, which may be a result of lower fitness of late breeders, as well as the effect of the intensity of Philornis infestation, with the temperature increase. The mean productivity was 0.77 young per pair, producing a single brood per breeding season (with the exception of two pairs that lost their brood and tried twice). Finally, we analyze the existence of hybrids between S. hypoxantha and S. melanogaster based on one individual monitored for two consecutive years at the study site. This individual had vocalizations completely consistent with the pattern of S. hypoxantha and plumage as in S. melanogaster, although it may represent a typical case of interspecific song learning. This pattern has never been observed previously.